Lyotropic liquid crystalline phthalocyanines containing 4-((S)-3,7-dimethyloctyloxy)phenoxy moieties - Korkut, Sibel Eken; Ocak, Hale; Bilgin-Eran, Belkis; Guzeller, Dilek; Sener, M. Kasim (WORLD SCI PUBL CO INC, 2017)
The novel metal free phthalocyanine and its copper complex which are octa-substituted at the peripheral positions with 4-((S)-3,7-dimethlyoctyloxy) phenoxy moieties were synthesized and characterized by FT-IR, H-1 NMR and mass spectroscopy. Their mesomorphic properties were studied by polarizing optical microscopy. The spectroscopic properties and aggregation behaviors of the novel phthalocyanines were also investigated by UV-vis spectroscopy in different solvents with same concentration as well as in a wide range of concentrations of chloroform. Both compounds with chloroform and n-dodecane clearly show the lyotropic columnar mesophase in a wide temperature range whereas thermotropic liquid crystalline behavior for both compounds is not observed. Both of these novel compounds show no aggregation in toluene, tetrahydrofuran, dichloromethane and chloroform
Keywords: phthalocyanine; liquid crystalline; lyotropic mesophase; copper; TRANSITION-METAL-COMPLEXES; SUPRAMOLECULAR STRUCTURE; MOLECULAR MATERIALS; PERIPHERAL CHAIN; DERIVATIVES; MESOPHASE; BEHAVIOR; SUBSTITUENTS; MESOMORPHISM; POSITION; Chemistry